Adjunctive Relaxation Modalities (Deep Breathing and Murottal Therapy) For Pain and Hypertension Control in Non-ST-Elevation Myocardial Infarction (NSTEMI): A Case Study - Rita; Hanida Hani Mohd Mokhtar; Fitri Arofiati; Noor Hanita Zaini (INTERNATIONAL JOURNAL OF CARE SCHOLARS, 2026)
Abstract Background: NSTEMI is an acute coronary syndrome characterized by elevated cardiac biomarkers without persistent ST-segment elevation. This syndrome carries a high risk of mortality in elderly patients with hypertension. This can increase the workload of the heart and trigger ischemia due to extreme blood pressure and an imbalance in oxygen supply and demand. Objective: To explore the application of evidence-based nursing interventions in the management of chest pain in patients with Non-ST-Elevation Myocardial Infarction (NSTEMI) with hypertensive emergencies. Case: A 77-year-old man with NSTEMI and a hypertensive emergency presented with chest pain, shortness of breath, and nausea. Initial examination revealed a blood pressure of 201/100 mmHg, an ECG with ST-segment depression and T-wave inversion in the inferior leads, troponin I level (40,065 pg/mL). Pharmacological therapy fondaparinux, atorvastatin, plavix, cardiprin, pantoprazole, starting perindopril. Serial monitoring revealed a decrease in chest pain score (from 7 to 4), a gradual decrease in blood pressure (from 201/100 mmHg to 152/95 mmHg). Discussion: This case emphasizes the importance of comprehensive management of NSTEMI with hypertension, including blood pressure control, therapy according to guidelines, and evidence-based nursing interventions. Deep breathing relaxation techniques and murottal therapy have been shown to be effective in reducing chest pain, decreasing anxiety, and improving physiological function by increasing oxygenation and the relaxation response. Conclusion: Management of NSTEMI with hypertensive emergencies requires an integrated approach, including guideline-based medical therapy and evidence-based nursing interventions. Deep breathing techniques and murottal therapy have been proven effective in reducing pain, stabilizing hemodynamics, and improving quality of life in elderly patients. Keywords: NSTEMI, hypertensive emergency, chest pain, relaxation techniques, murottal therapy